Cloud Computing's Use in Medical Science - Thamizhselvi, D; Ragavi, M; Nivetha, K (2021 4th International Conference on Computing and Communications Technologies (ICCCT), 2021)
In recent decades, technology has grown rapidly with advances in science. Doctors can store data on their critical illnesses, complex cases, and sophisticated problems using cloud computing. Since the advent of cloud computing, it has been possible to solve many complex problems very quickly and at a lower cost. Many doctors use cloud computing to solve their problems. The paper discusses how cloud computing technology is used in the medical field, particularly in hospitals where computers are indispensable to better treating diseases.